In Situ Trametes versicolor Laccase Biocathode Performance Assessment in Dual-Chamber Microbial Fuel Cells - Ottoni, Cristiane [UNESP]; do Valle Trotta, Caterina [UNESP]; Martins, Gilberto; Matos, Joana; Maiorano, Alfredo Eduardo; Brito, António G.; Peixoto, Luciana (Springer Nature, 2023)
White-rot fungi (WRF) synthesize ligninolytic extracellular oxidative enzymes such as laccase (Lcc), which has been described as one of the most interesting types of redox enzymes that can improve microbial fuel cell (MFC) performance. Therefore, and in order to test that performance, WRF Trametes versicolor MUM 04.100 was immobilized in nylon sponge and fixed in the MFC cathode chamber, while Lcc activity, bioelectricity production, and organic matter removal were monitored. It was found that current density measured in the MFC supplemented with fungi was 2.1 times higher (42.81 ± 4.91 mA/m2) than current density obtained in the control MFC (absence of fungus in the cathode chamber, 20.31 ± 4.30 mA/m2). Maximum Lcc activity (23.08 U/L) and the highest value of organic matter removal (COD) (92%) from domestic wastewater was obtained on the last cycle after biofilm maturation and glycerol pulse. This work evidences that Lcc continuously synthesized by MUM 04.100 immobilized in the biocathode is a promising approach to enhance MFC power performance and wastewater treatment.
Keywords: Bioelectricity; Fungal enzyme immobilization; Glycerol; Municipal wastewater